2019
DOI: 10.1111/acel.13006
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte‐like nested cells in the aged intervertebral disc are late‐stage nucleus pulposus cells

Abstract: Aging is a major risk factor of intervertebral disc degeneration and a leading cause of back pain. Pathological changes associated with disc degeneration include the absence of large, vacuolated and reticular‐shaped nucleus pulposus cells, and appearance of smaller cells nested in lacunae. These small nested cells are conventionally described as chondrocyte‐like cells; however, their origin in the intervertebral disc is unknown. Here, using a genetic mouse model and a fate mapping strategy, we have found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 20 publications
4
72
1
Order By: Relevance
“…This result suggests that NP cell vacuoles may contribute to the DHI measurement. Cell size is particularly relevant to degenerative disc disease, because smaller chondrocyte‐like cells are associated with aging and degeneration . The increase in cell band size in the lumbar region is consistent with a recent study involving overexpression of TNFα.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result suggests that NP cell vacuoles may contribute to the DHI measurement. Cell size is particularly relevant to degenerative disc disease, because smaller chondrocyte‐like cells are associated with aging and degeneration . The increase in cell band size in the lumbar region is consistent with a recent study involving overexpression of TNFα.…”
Section: Discussionsupporting
confidence: 88%
“…Low back pain (LBP) and associated intervertebral disc degeneration is a widespread, costly, and complex medical condition affecting a huge proportion of the population . As the disc degenerates with age or disease, the nucleus pulposus (NP) becomes more fibrotic, and cells transition from a vacuolated notochordal phenotype to one that resembles hypertrophic chondrocytes . In concert with these cellular and extracellular matrix changes, the dramatic increase in interleukin‐1β (IL‐1β) and tumor necrosis factor alpha (TNFα) expression is correlated with severity of disc degeneration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 A more recent article has found that chondrocyte-like cells are derived from disc NP cells during degeneration, the phenotype of which represents a terminal stage of differentiation preceding the loss of NP cells and disc collapse. 11 Notochordal cell-conditioned medium protects non-notochordal cells from apoptosis and inflammation. 12 In addition, notochordal cells produce larger amounts of proteoglycans than non-notochordal cells 13 and can stimulate non-notochordal cells to produce proteoglycans.…”
Section: Pathophysiology Of the Intervertebral Discmentioning
confidence: 99%
“…Notochordal cells only exist during the first 10 years of human life and are subsequently replaced by non‐notochordal, chondrocyte‐like cells of unknown provenance . A more recent article has found that chondrocyte‐like cells are derived from disc NP cells during degeneration, the phenotype of which represents a terminal stage of differentiation preceding the loss of NP cells and disc collapse . Notochordal cell‐conditioned medium protects non‐notochordal cells from apoptosis and inflammation .…”
Section: Introductionmentioning
confidence: 99%